July effect in hospitalized cirrhosis patients: A US nationwide study using difference-in-differences analysis - Melis Gokce Celdir; George Wehby; Shahana Prakash; Tomohiro Tanaka (PLoS ONE, 2025)
Background The July effect in US teaching hospitals has been studied with conflicting results. We aimed to evaluate the effect of physician turnover in July on the clinical outcomes of patients hospitalized with cirrhosis. Methods We utilized the Nationwide Inpatient Sample database (2016–2019) to identify patients hospitalized with cirrhosis and liver-related complications (variceal bleeding, hepatorenal syndrome, acute-on-chronic liver failure). We used difference-in-differences analysis to compare teaching and non-teaching hospital differences in mortality and length of stay (LOS) in May and July, and trends in outcomes in other months before and after July. Results We included 78,371 hospitalizations in teaching and 23,518 in non-teaching hospitals in May and July. Teaching hospital admissions had overall higher complication rates and mortality compared to non-teaching hospitals. We did not find a difference in mortality between teaching and non-teaching hospitals in all cirrhotic patients (adjusted odds ratio 1.01, 95%CI [0.88–1.16]) or in those with severe complications (0.87, [0.72–1.06]). There was greater LOS in July vs. May in teaching hospitals relative to non-teaching hospitals for all patients with cirrhosis (adjusted rate ratio 1.03, 95%CI [1.02–1.05]) and for those with severe complications (1.19, [1.17–1.21]). The months after July were associated with longer LOS in teaching hospitals, with the effect gradually diminishing over the subsequent months. Conclusions Our study suggests trainee turnover in July did not affect mortality, but lengthened hospital stays for patients with cirrhosis, highlighting the need for effective supervision of new trainees and strategies to mitigate operational disruptions for improved clinical management.